IMPLEMENTASI KEBIJAKAN SUSTAINABLE DEVELOPMENT GOALS DALAM PENUNTASAN KEMISKINAN DI DESA SUNGAI KUNYIT HULU KABUPATEN MAMPAWAH - -, Doef; Hardianto, Willy Tri; Suprojo, Agung (Jurnal Ilmiah Publika, 2023)
One of the development programs that the Government of Indonesia has taken seriously is the Sustainable Development Goals (Village SDGs). This program modifies the concept of global SDGs that was launched by the United Nations (UN) on September 25, 2015. While the global SDGs has 17 main points to create a sustainable living scheme, the main problem in Mempawah is the lack of active role of the village government apparatus in the implementation of the SDGs policy itself. The purpose of this research is to find out whether there is an effective application through policy or program. This type of research uses qualitative research. According to Bogdan and Taylor in Moleong (2014: 4) qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior according to them this opinion is directed at the setting and the individual holistically (whole). The results of this study are the implementation of the Sustainable Development Goals (SDGs) policy in poverty reduction in Sungai Kunyit Hulu Village, Mempawah Regency after seeing firsthand that it is effective even though it only depends on a few personnel. So researchers must play a more active role in implementing the policy.